Stability analysis in a soliton fiber ring laser with a hybrid saturable absorber - Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Lim, K.S.; Ahmad, Harith (John Wiley & Sons, 2013)
A stable mode-locked fiber laser having two rejection ports employing a 4 m long erbium doped fiber is demonstrated. Near transform limited short pulses with a repetition rate of 8.27 MHz are obtained at a wavelength of 1565 nm by using a slow saturable absorber. The pulse width can continuously vary from 1.2 ps to less than 130 fs with a maximum spectral width of 20 nm. Although the changes of the pulse duration over one round-trip in the resonator is small. However, a comparison of the energy fluctuations from coupler port toward polarizing beam splitter (PBS) port reveals that energy fluctuation is varied from 4.1% to 7.8% and stronger for PBS port. We also find that the low frequency timing jitter for a fixed pump power is stronger for PBS port and the high frequency timing jitter at PBS port is more than twice larger than that of the timing jitter at coupler port. By removing fiber adapters and controlling the environmental airflow in the setup, timing jitter was reduced by an order of magnitude.